Enhancing Workers’ Safety in Manufacturing : A Human-Centered Approach in Interaction Design of Digital Training Tools - Vigoroso, Lucia; Alce, Günter; Boccadutri, Luca; Caffaro, Federica (Springer Series in Design and Innovation, 2025)
Digital innovation offers promising avenues for accessible, engaging, and user-friendly training solutions, crucial for promoting safety among manufacturing workers. However, optimizing these solutions demands a profound understanding of workers’ needs and preferences in interacting with these digital systems. The ongoing “DigiSafeMan” project aims to develop a prototype of a digital training tool tailored to manufacturing workers, adopting a Human-Centered Design approach. The present study focused on context and user needs analysis, involving the examination of secondary data on accidents and training activities at a selected firm in the Piedmont region (Italy), as well as semi-structured interviews with 26 workers to explore their risk perceptions, training priorities, and feedback on game features and design. Results highlighted prevalent injuries and the need to improve in current safety training methods. Participants prefer interactive, visually engaging materials, emphasizing video content and intuitive interfaces. Concerns arose about potential motion sickness from a 360° panorama image. This research phase laid the foundation for a human-centered, innovative, and sustainable digital safety training tool.
Keywords: Human-Centered Design; Interaction design; Manufacturing industry